A NOTF ON AN INEXPENSIVE CORACLE - Parameswaran, S; Murugesan, V K (Indian Journal of Fisheries, 2011)
The note deals wifi the construction of both conventional and inexpensive coracles and the advantages of the latter, in which the costly leather is replaced by cheaply available, syrtttietic, woven sack material.